2011
DOI: 10.1523/jneurosci.5671-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Potentiation of Excitatory Inputs to Ventral Tegmental Area Dopamine Neurons

Abstract: Drug-induced changes in synaptic strength are hypothesized to contribute to appetitive behavior and addiction. Nicotine, the major addictive substance in tobacco, activates nicotinic receptors (nAChRs) to initiate a series of adaptive changes at the cellular and circuit levels in brain, particularly the ventral tegmental area (VTA). Our lab previously reported that nicotine facilitates induction of long-term potentiation (LTP) in VTA dopamine (DA) neurons by increasing glutamate release via activation of α7 nA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 40 publications
3
76
0
Order By: Relevance
“…6, B and C). Previous studies indicate that DA D1/ D5 receptors in VTA may play a role in altered synaptic plasticity after exposure to drugs of abuse (Gao and Wolf, 2007;Mao et al, 2011). Blockade of DA D1/D5 receptors with SCH23390 (10 mM) did not appear to substantially reduce nicotine-mediated enhancement in AMPA-evoked currents (SCH23390 5 2325.06 44.7 pA; Fig.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…6, B and C). Previous studies indicate that DA D1/ D5 receptors in VTA may play a role in altered synaptic plasticity after exposure to drugs of abuse (Gao and Wolf, 2007;Mao et al, 2011). Blockade of DA D1/D5 receptors with SCH23390 (10 mM) did not appear to substantially reduce nicotine-mediated enhancement in AMPA-evoked currents (SCH23390 5 2325.06 44.7 pA; Fig.…”
Section: Resultsmentioning
confidence: 73%
“…Slices were cut and allowed to recover for 60 minutes, followed by exposure of the slices to 100 nM nicotine (or a control solution containing no nicotine) for 60 minutes similar to previous studies Mao et al, 2011) (Fig. 4A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the present study examined cellular and molecular events of PDLSCs using an experimental model, which can represent tobacco product, nicotine-mediated periodontal disease. Nicotine is a lipophilic molecule of which the effects on neuronal nicotinic acetylcholine receptors (nAChR) have been primarily focused on its physiologic impact within the confines of the nervous system (Mao et al, 2011). However, many studies have recently found neuronal nAChRs to be expressed on many different non-neuronal cell types throughout the body (Chernyavsky et al, 2005;Resende et al, 2008;Wang et al, 2010;Wessler and Kirkpatrick, 2008).…”
Section: Discusstionmentioning
confidence: 99%
“…Feduccia et al (2012) in their review added new insights to the function of nicotinic acetylcholine receptors (nAChR) in alcohol and nicotine addiction. The nAChRs are ligand-gated ion channels which are wildly distributed in the brain and play a crucial role in synaptic neurotransmission (Mao et al, 2011). Both alcohol and nicotine are able to activate neuronal nAChRs.…”
mentioning
confidence: 99%